The study on Malaysian online shopping platform in cosmetic business affect toward dependency on human capital - Yusmawati Binti Hussain (2018)
Online shopping is defines when the people buying the good using the internet as the medium.According by Liang and Huang (1998) stated that the variety kind of products types give effect on acceptance of online shopping by the consumer.The variety of product can be buy using the online shopping,that why it been called the online mall. Examples of the famous of the online shopping are LAZADA,ZALORA and SHOPEE.Majority of the Malaysians people’s using this medium in order to shopping because it saves the time and faster.According by Eugene Mahalingam (2016) says that online shopping is became trends in Malaysia.The increasing of the online shopping can give effect for the residents in term of the challenges in the opportunity of job and when there is too much of development in the online business.This research will more focussing for the implication of online shopping toward human capital and when there is too much transaction using online it can lead for the digital business that can give some effect for the community.This research study will touch about the how online shopping can give effect for the surrounding people and also how far this problem. With the research study the detail and specific of information about online shopping will be obtain and can be used in order to create full idea of the research.